Women Perception as Cockle Cultivator Households - Novriani, Aminia; Fatchiya, Anna (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2011)
Sustainable development of coastal and marine resources in Indonesia reveals that women take an important role in coastal and marine sectors. This study focused on women's perception of their role. It aimed to assess the women’s perception about their role and to analyze the relationship between internal and external factors with women's perception about their role in cockle cultivator households. This study applied survey method with quantitative approach which is supported by qualitative information. The result of this study found that most respondents are in middle adulthood (31-50 years), have low education levels, low income levels, has a job as “ pengitri k” and Bugis tribes. The results of descriptive analysis showed that women's perception of their role in the household tend to be less good, it means respondents did not have a conscious view of gender in almost aspects of household roles. The results of statistical analysis showed that internal factors which is income level and employment has significantly related to women’s perceptions about their role in the household. Another factors such as age, education, and income has not significantly related to the women’ s perception. External factors in this study such as husband’s age, husband's education level and husband’s income level is not significantly related to the women's perception of their role in the household. Keywords: women’s p erception, cockle cultivator households, gender